Anti-fertility effect of fenugreek seeds aqueous extract on female rats - Abdi, Mohamed Yehdih Amar (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Anti-fertility agents have been used since long time to prevent pregnancy. Nowadays, Oral Contraceptive Pills are the most common and efficient tool despite their side effects. With the progress in therapeutic sciences, natural components from different herbs are likewise used. Trigonella foenum-graecum is one of the used herbs. The purpose of the present study was to evaluate the anti-fertility effect of fenugreek seeds aqueous (FSA) extract on female rats by assessing the relative ovarian weight as well as relative uterine weight, counting the ovarian follicles (secondary, graafian, atretic follicles and corpora lutea) and measuring uterine endometrium thickness. Fourteen cyclic Sprague Dawley female rats, aged between 7 to 9 weeks, were randomly divided into two groups (control and treated). Animals in control group do not receive any treatment while those in treated were treated with 1500 mg/kg body weight fenugreek seeds aqueous extract. The extract was given orally to the treated rats for two weeks in a row. A vaginal smear was daily collected and examined from each rat to determine the different estrous cycle phases. After anesthetizing the rats, uterus and both ovaries were collected for histological examination. The administration of FSA extract has not shown significant reduction in the relative ovarian weight, however the reduction in uterine relative weight was statically significant. The secondary and graafien follicles were not significantly reduced. The increase in the number of atretic follicles was significant and the number of corora lutea shwed a significant reduction. The uterine endometrium thickness was in normal range. FSA extract showed anti-fertility effects by disturbing folliculogenesis and by causing histopathological changes in the uterine and ovarian tissues.